The difference of canine, first and second premolar tooth size resulted from cone beam computed tomography imaging with Moyers Prediction Table on the working study model - Julies Hariani Sugiaman; Bergman Thahar; Endah Mardiati; Ria Noerianingsih Firman (Padjadjaran Journal of Dentistry, 2011)
Model study is one of the standard orthodontic components which is important for diagnosis and treatment plan, but in some patients with the high gag reflex, it will be difficult to get this kind of study models. The existence of a new device which is able to show the condition of patients' mouth in three space areas (axial, sagittal, and coronal) is expected to be an alternative when a study model is difficult to get. The purpose of this study is to find out whether or not there are any differences on the size of canine's mesiodistal, first and second premolar resulted from CBCT imaging with Moyers analysis on the study models. The method of the research is comparative descriptive. Measurements are made on 10 CBCT imaging results and 10 study models. The mesiodistal size, the result of CBCT imaging is measured by the available computer program and also the mesiodistal size of the study models is measured using a sliding compass, and then the size of canines, first and second premolar teeth resulted from CBCT imaging are compared to the result of Moyers method analysis on the study models. The t-test is used to find out if there is a difference between teeth size value between the CBCT imaging with the study models. The significance is determined based on the p-value < 0,05. The statistical test result shows a significant difference between the size of canines mesiodistal, first and second premolar teeth, the result of CBCT imaging and the Moyers analysis result in the study models in which t count > t table.